QGIS geoprocessing model to simplify first level seismic microzonation analysis - Cosentino, Giuseppe; Pennica, Francesco (PeerJ Preprints, 2016)
The seismic microzonation evaluate the seismic hazard at the local scale proposing to identify areas of territory characterized by homogeneous seismic behaviors. The first level of seismic microzoning has the purpose of defining the lithological properties and geometry of geological units that characterize these portions of territory (microzones). The scope of this work is to contribute to the creation of a geoprocessing methodology for topographical, geological, geophysical and geo-technical data aimed at level 1 seismic microzonation map drafting. A QGIS geoprocessing tool was designed to automate one of the analysis commonly performed for the creation of level 1 seismic microzonation maps, in particular to identify unstable zones as polygon features. The result is a polygon layer with areas prone to instability due to a slope value greater than 15 degrees.
Keywords: GIS; seismic microzonation; seismic hazard; geoprocessing